Analisis Teori-Teori Belajar pada Pengembangan Model Blended Learning dengan facebook (MBL-FB) - Asmendri, Asmendri; Sari, Milya (Natural Science: Jurnal Penelitian Bidang IPA dan Pendidikan IPA, 2018)
The research objective is to analyze learning theories that support the development of blended learning models with Facebook (MBL-fb). The research method uses library research. The results of the study can be seen that learning theories that support the development of blended learning models are cognitive learning theories, constructivism and Connectivism. Social cognitive suggests that there are three main factors: behavior, person / cognitive, and the environment that influence one's learning process. Information processing explains the thinking process of students in processing information, monitoring it, and developing strategies regarding the information. Personal constructivists state that students construct knowledge by informing, organizing, and reorganizing prior knowledge and information. Social constructivists explain that knowledge is built and constructed together. Constructivism, knowledge is distributed on a network of connections, and therefore learning consists of the ability to build and traverse the network.